Manim como ferramenta didática para potencializar o ensino de cálculo - Fiori, Kallel Vinicius Rocha (Universidade Federal de São Carlos, 2024)
Visualization in Mathematics is an area of research that studies visual elements in computational tools, such as graphs, diagrams and geometric representations to communicate certain mathematical content that can assist in Teaching. In the computational context, Manim is a Python library designed for creating high-quality graphical animations and mathematical objects. With the aim of exploring the use of Manim considering aspects of Mathematical Visualization in Teaching contexts, this Course Completion Work (i) reviewed the literature on Computer Visualization from the perspective of Diehl (2005), (ii) compared aspects of Mathematical Visualization between Manim and Geogebra and (iii) developed teaching material that can assist the teacher in Teaching Differential Calculus. Results show that Manim stood out as an effective tool in the educational context, with a high level of granularity and reuse capacity, being adaptable to different perspectives and educational needs.
Manim as a didactic tool to enhance the teaching of calculus
Keywords: Python; Manim; Ensino de cálculo; Visualização matemática; Teaching calculus; Mathematical visualization; CIENCIAS EXATAS E DA TERRA::MATEMATICA